Effect of emission current delay on the efficiency of electron beam production - Egorov I. S. Ivan Sergeevich; Remnev G. E. Gennady Efimovich; Poloskov A. V. Artem Viktorovich; Serebrennikov M. A. Maksim Anatoljevich (2017, 2017)
Title screen